Co-selecting students for more democratic co-creation: A case study from the Create a Subject Challenge - Post, Ger; Nguyen, Lily; Tan, Jiang Li; Lim, Saw Hoon; Paquet-Fifield, Sophie; Barrese, Michael; Clark, Charlotte (International Journal for Students as Partners, 2023)
Democratic processes are at the foundation of the students-as-partners (SaP) framework. Student selection for SaP projects however, is typically in the hands of staff, which is undemocratic and faculty assumptions and practice exclude particular students from co-creation projects. We describe a case study in which students and staff jointly select students for a co-creation project in the School of Biomedical Sciences at the University of Melbourne. Our reflections suggest that co-selection, compared to selection of students by staff alone, further realizes the democratic ideal of SaP by integrating the student perspective early in the co-creation process. We reflect on the democratic processes in our case study through the lens of deliberative democracy and share prospects and perils of voting and deliberation to embed the student voice in student selection for co-creation.